Sentencing in Narcotics Criminal Offenses from the Perspective of Certainty and Justice - Laia, Sri Wahyuni; Panggabean, Mompang L. (JURNAL AKTA, 2024)
This study investigates the sentencing practices in narcotics criminal cases, focusing on whether they align with the principles of legal certainty and justice. The central aim is to examine whether judges' rulings in such cases uphold the legal norms established in existing legislation, particularly in relation to mandatory minimum sentences and the cumulative imposition of penalties, such as imprisonment and fines. The research employs a normative or doctrinal legal method, analyzing legal statutes, court decisions, and legal commentaries related to narcotics offenses. By scrutinizing the sentencing framework, the study seeks to understand how legal norms influence judicial discretion and the extent to which sentencing practices maintain consistency with established laws. A key focus is on the potential discrepancies between in abstracto (legislation) and in concreto (court rulings), particularly when judges deviate from the minimum sentencing guidelines. This research is significant as it explores the balance between strict legal enforcement and the need for justice that considers the circumstances of each case. The findings are expected to contribute to ongoing discussions on legal reform, helping to develop a sentencing system that is both fair and consistent, ensuring that legal certainty and justice are upheld in narcotics-related offenses.